Α1‐Antitrypsin Z allele and risk of venous thromboembolism in the general population. (30th October 2021) - Riis, Julie; Nordestgaard, Børge G.; Afzal, Shoaib
Abstract: Background: The α1 ‐antitrypsin Z (rs28929474) allele may lead to alterations in hemostasis either through liver disease or effects on coagulation factors. Objectives: To test the hypothesis that the α1 ‐antitrypsin Z genetic variant is associated with increased risk of venous thromboembolism. Methods: A total of 107 075 individuals from the Copenhagen General Population Study were used to test the association of the α1 ‐antitrypsin Z genetic variant with risk of venous thromboembolism, including deep venous thrombosis and pulmonary embolism, prospectively. Confirmatory analyses were done in the UK Biobank. Results: During follow‐up, venous thromboembolism was diagnosed 6649 times in noncarriers, 436 times in heterozygotes, and 10 times in homozygotes. Hazard ratios for venous thromboembolism in α1 ‐antitrypsin Z heterozygotes and homozygotes versus noncarriers were 1.1 (95% confidence interval, 1.0–1.2) and 2.2 (1.3–3.7). A one Z allele increase was associated with a hazard ratio for venous thromboembolism of 1.2 (1.0–1.3). The corresponding odds ratio in the UK Biobank was 1.2 (1.1–1.3). The absolute risk of venous thromboembolism associated with α1 ‐antitrypsin ZZ homozygosity was 7.8% (3.6–12.1). The corresponding estimates were 20.1% (9.1–31.2) for prothrombin G20210A and 15.0% (12.6–17.4) for factor V Leiden. The fraction of venous thromboembolic events attributable to the α1 ‐antitrypsin Z allele was 0.7% (0.1–1.3). For the prothrombin G20210A and factor V Leiden mutations, population attributable fractions were 1.2% (0.9–1.6) and 10.5% (9.9–11.1). Conclusion: In conclusion, α1 ‐antitrypsin ZZ homozygosity was associated with a 2.2‐fold risk of venous thromboembolism and had a comparable population attributable fraction to prothrombin G20210A.